Green Technologies to Improve the Environment on Earth 2019
DOI: 10.5772/intechopen.82359
|View full text |Cite
|
Sign up to set email alerts
|

How Technology Can Transform Wildlife Conservation

Abstract: Wildlife is under threat from various kinds of human activities, such as habitat destruction, illegal wildlife trade, spread of invasive species and diseases, and from the human impact on the Earth's climate, which is changing the nature of wild habitats. Advances in technology give conservationists, scientists, and the general public the advantage to better understand the animals, their habitats, and the threats they can face. In this chapter, I provide a review of the benefits of the use of technology to ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…More investigation into this is warranted. Concerns regarding adverse effects of technology on animalbased tourism have increased together with the exponential improvement of technology (Pacheco, 2018;Essen et al, 2020). In our case study, we found that light from flashlight and mobile phones that tourists use force the shrimp to walk back to the river which results in them getting washed downstream.…”
Section: Discussionmentioning
confidence: 81%
“…More investigation into this is warranted. Concerns regarding adverse effects of technology on animalbased tourism have increased together with the exponential improvement of technology (Pacheco, 2018;Essen et al, 2020). In our case study, we found that light from flashlight and mobile phones that tourists use force the shrimp to walk back to the river which results in them getting washed downstream.…”
Section: Discussionmentioning
confidence: 81%
“…Conservation technology is being developed for animals in both natural environments and captive settings (e.g. foxes in urban settings and elephants in zoos, respectively) [ 17 ] and may also be applied to plants, habitats and geological phenomena.…”
Section: Background and Motivationmentioning
confidence: 99%
“…They include mammals, birds, and bees. Wild animals encompass free-range wildlife, migratory wildlife, captive wildlife (animals in zoos and wildlife parks), and feral animals (wild pigs, Sus scrofa) [58,59].…”
Section: Wild Animals In Zoos Parks and Free Range; Role In The Epide...mentioning
confidence: 99%